Extrativos de Piper gaudichaudianum Kunth no controle de fungos apodrecedores da madeira - Bianchini, Nadia Helena (2022)
The search for alternative methods to preserve wood has been stimulated due to the high toxicity of conventional products. Research related to the use of essential oils (EOs) as an alternative treatment has increased in recent years due to their wide applicability. The aim of this study was to evaluate the antifungal activity of plant extractives obtained from different parts (leaves, stems and roots) of Piper gaudichaudianum Kunth (Piperaceae) to control the growth of wood-rotting fungi in vitro, and to elucidate one of the action mechanisms of the essential (EO) and its major compound (dillapiole). Additionally, a stable nanoemulsion was developed from the EO of leaves of this species and a stability study was performed, in addition to evaluating whether the collection site influences the chemical composition of the EO. The EO was obtained by hydrodistillation of different parts of P. gaudichaudianum, with a modified Clevenger-type apparatus. Then, extraction yield, density and chemical composition were determined, by gas chromatography coupled to mass spectrometry (CG-MS) and gas chromatography with flame ionization detection (CG-FID). Dillapiole was isolated from the leaves EO by 2 chromatographic columns, performed in sequence. The extracts were obtained by extraction under reflux, with Soxhlet apparatus. The antifungal potential of plant extracts was verified against Ganoderma applanatum (Pers.) Pat. (white-rot) and Lentinus lepideus (Fr.) (brown-rot). Additionally, the content of ergosterol in the mycelia plasma membrane was evaluated under the effect of dillapiole and leaves EO of this species. The nanoemulsions were prepared using the high energy emulsification method. The results showed that the EO of P. gaudichaudianum leaves showed antifungal activity against the rotting fungi evaluated, where L. lepideus showed greater susceptibility to the effect of extractives, which showed a fungicidal effect. The results also indicate that dillapiole showed greater inhibition of mycelial growth in fungi compared to EO at the corresponding concentration (P < 0.05). Additionally, EO and dillapiole reduced the content of ergosterol in the fungal mycelium of the species evaluated. Regarding the extracts, the extraction yields are specific for each organ of the plant and depend directly on the solvent used. Among the results of antifungal activity, those obtained with roots hexane extract at the highest concentration evaluated inhibited 73.90 ± 0.182% of the mycelial growth of G. applanatum and 91.44 ± 5.416% of L. lepideus mycelial growth. Regarding the chemical composition of the EO, according to the hierarchical cluster analysis and the analysis of principal components, there was no difference between the EO constituents of leaves and branches collected at the same location. However, the EO density of branches was lower than for the EO of leaves (P = 0.0011). Additionally, there was a difference between the chemical composition of EO from leaves collected in different regions, while the components of EO from roots did not differ. A stable nanoemulsion was developed from the EO of P. gaudichaudianum leaves, with the appropriate nanometric parameters when stored at room temperature or under refrigeration.